High School Graduation Quadrille – a Contemporary Dance Ritual - Zdravkova-Djeparoska, Sonja (University Publishing Hause “Neofit Rilski”, 2016)
Social practice has proved that certain dance forms occasionally transit in relation to their role in society, thus obtaining new meanings. Quadrille is a dance that typically belonged in 19th century social events. However, beginning with the practice initiated by the dance club “Urshka” from Slovenia in 2001, quadrille has become a contemporary dance ritual practiced by the youth. High school graduates gather on a predetermined date (in the second half of May) outdoors – on a square, in a wider street – and they dance quadrille. The idea behind these performances is to popularize the event and to increase the number of countries that participate in this event. At present this list covers Slovenia, Croatia, Serbia, Macedonia, Bulgaria, Albania, Montenegro, Ukraine, Bosnia and Herzegovina and Romania. The quadrille starts at the same time for all the performers in all the countries, and they all dance an identical choreography. Macedonia joined this event in 2007 and the number of participants is growing up every year. This kind of “contemporary ritual of the initiation" has several functions: it denotes high school graduation, completion of the second level of education, at the same time marking the collective age of maturity. Further, it unites the youth into one single common idea. This dance event is especially important for the community where it takes place, which is obvious from the wide media coverage of the event (announcements in the newspapers, reports, interviews, and so on.). The performance of the high school graduation quadrille has entered the Guinness book of records. Quadrille –a ballroom dance, is slowly turning into a modern phenomenon practiced in current, modern spheres of the society, through which the high school graduates from southeastern Europe identify and present themselves.
Keywords: Macedonia; quadrille dance; contemporary rituals; high school graduates.